Anaphylactic cardiovascular collapse manifesting as myocardial infarction following salad consumption. A case of Kounis variant type I syndrome. - Vaina, Sophia; Chrysohoou, Christina; Bonfanti, Laura; Kounis, Nicholas George; Cervellin, Gianfranco; Georgiopoulos, Georgios; Tousoulis, Dimitris (Acta Biomedica Atenei Parmensis, 2020)
Anaphylactic cardiovascular events constitute an underrated cause of medical emergencies in hospitalized patients. Coronary arteries and myocardium are targeted by anaphylactic mediators leading to acute coronary syndrome and imminent cardiovascular collapse. Early diagnosis and high clinical suspicion are required to secure prompt life-saving treatment in these cases. However, physicians of both Cardiology and Internal Medicine Departments are not familiar with this condition. Recently, we diagnosed and treated a case of anaphylactic cardiovascular collapse manifesting as acute myocardial infarction following salad consumption. Notably, Kounis anaphylaxis-associated acute coronary syndrome is a rare cause of ST segment elevation myocardial infarction with normal or diseased coronary arteries. We recommend that Kounis syndrome and its variants should be taken into consideration in the differential diagnosis of ischemic heart disease in patients with signs of allergic reaction and/or medical history of previous allergic reactions, who experience acute coronary syndrome after exposure to certain environmental stimuli.